2018
DOI: 10.1093/biolre/ioy145
|View full text |Cite
|
Sign up to set email alerts
|

Action of neurotensin, corticotropin-releasing hormone, and RFamide-related peptide-3 in E2-induced negative feedback control: studies using a mouse arcuate nucleus hypothalamic cell model†

Abstract: The recently established immortalized hypothalamic cell model mHypoA-55 possesses characteristics similar to those of Kiss-1 neurons in the arcuate nucleus (ARC) region of the hypothalamus. Here, we show that Kiss-1 gene expression in these cells was downregulated by 17β-estradiol (E2) under certain conditions. Both neurotensin (NT) and corticotropin-releasing hormone (CRH) were expressed in these cells and upregulated by E2. Stimulation of mHypoA-55 cells with NT and CRH significantly decreased Kiss-1 mRNA ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Other experimental paradigms indirectly suggest a possible influence of E2 on RFRP-3 neurons. For example, E2 treatment increases RFRP-3 synthesis in the hypothalamic mHypoA-55 rat cell line (111). In Syrian hamsters, food-restriction increases the percentage of RFRP-3 cells expressing c-Fos , with increased ovarian steroids at the time of estrus abolishing the impact of food restriction on RFRP-3 cellular activation (112).…”
Section: Rfrp-3 Contributes To the Daily Rhythm Of Reproduction In Fementioning
confidence: 99%
“…Other experimental paradigms indirectly suggest a possible influence of E2 on RFRP-3 neurons. For example, E2 treatment increases RFRP-3 synthesis in the hypothalamic mHypoA-55 rat cell line (111). In Syrian hamsters, food-restriction increases the percentage of RFRP-3 cells expressing c-Fos , with increased ovarian steroids at the time of estrus abolishing the impact of food restriction on RFRP-3 cellular activation (112).…”
Section: Rfrp-3 Contributes To the Daily Rhythm Of Reproduction In Fementioning
confidence: 99%
“…mHypoA-55 cells originated from mouse hypothalamic Kiss-1 neurons located in the ARC. These cells were defined as KNDy neurons because they express NKB (Tac3), DynA, and Kiss-1, and show a similar response to E2 stimulation on Kiss-1 gene expression [ 23 , 24 ]. Testosterone stimulation induced Kiss-1 gene and kisspeptin protein expression with a concomitant increase in Tac3 gene expression and NKB protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Kiss-1-expressing mHypoA-55 cells are a model of KNDy neurons that were isolated from the ARC of an adult female mouse. These cells co-express NKB, DynA, and Kiss-1, and Kiss-1 gene expression can be repressed in these cells by E2 under certain experimental conditions [ 23 , 24 ]. Using these cells, we investigated how androgens directly affect KNDy neurons in the hypothalamus.…”
Section: Introductionmentioning
confidence: 99%
“…Findings of this study showed that under the influence of estradiol along with RFRP‐3 expression, both NT and CRH had inhibitory effects on Kiss‐1 gene expression in the ARC kisspeptin neurons. 34 Thus we can assume that during non‐breeding season greater RFRP‐3 expression might enhance the NT and CRH expression both of which may inhibit kiss‐1 gene function reducing kisspeptin to GnRH, resulting in reproductive axis suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Our result of co-localization is consistent with a recent study, that found Furthermore, previous research showed that the hypothalamic ARC cell model (mHypoA-55) expressed kisspeptin, neurotensin (NT), corticotrophins-releasing hormone (CRH), and RFRP-3. 34 NT, a neuropeptide, notably express in AVPV and ARC area of mammals and has been shown to involved in feeding and reproductive functions. Similarly, CRH is largely synthesized in paraventricular nucleus and involved as a key processor for stress responses.…”
Section: Discussionmentioning
confidence: 99%